Who Sees Corruption? The Bases of Mass Perceptions of Political Corruption in Latin America. Issue 2 (August 2019) - Canache, Damarys; Cawvey, Matthew; Hayes, Matthew; Mondak, Jeffery J.
The capacity of citizens to see political corruption where it exists and to link such perceptions to evaluations of public officials constitutes an important test of political accountability. Although past research has established that perceived corruption influences political judgments, much less is known regarding the critical prefatory matter of who sees corruption. This article develops a multifaceted theoretical framework regarding the possible bases of perceived corruption. Experiential factors – personal experience and vicarious experience with bribery – mark the starting point for our account. We then incorporate psychological dispositions that may colour judgments about corruption and that may strengthen or weaken the links between experiences and perceptions. Expectations derived from this framework are tested in a series of multi-level models, with data from over 30, 000 survey respondents from 17 nations and 84 regions in the Americas.